Cloning and expression of rice glutamate decarboxylase (GAD) in Escherichia coli - Kariminik, A.; Saeidi, M.; Parsia, P. (Cellular and Molecular Biology, 2017)
Glutamate decarboxylase (GAD) converts L-glutamate to g-aminobutyric acid (GABA), which is a non-protein amino acid present in all organisms with some activities including improvement of neurve and cytoskeltal functions. Therefore, GAD is considered as a key molecule to use in molecular therapy of genetical human diseases. Accordingly, cloning of GADs from various plants is an important aim of researchers. The aim of this study was to clone rice (Oryza sativa L.) GADs in Escherichia coli (E.coli) MC 1061 bacterium.In this study, rice GADs was cloned in E.coli in both 37°C and 28°C. Two concentrations of Isopropyl-Î²-D-thiogalactoside (IPTG) (0.5mM and 1mM) were investigated in TB medium. Purification was done with Ni2+-nitrilotriacetic acid (NTA) resin in various concentration of imidasol. According to SDS-PAGE analysis, rice GADs was cloned and expressed successfully in E.coli MC 1061 bacterium and the most expression was done in 37°C and 0.5mM IPTG and the best concentration of imidasol was 100mM for purification step. Based on the results, rice GADs can be expressed in E.coli MC 1061 bacterium and, hence, it is a suitable way to produce the plant enzyme in industrial scales.